2019
DOI: 10.1029/2018jf004756
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Ice‐Free Conditions for a Perennially Ice‐Covered Antarctic Lake

Abstract: Although perennially ice‐covered Antarctic lakes have experienced variable ice thicknesses over the past several decades, future ice thickness trends and associated aquatic biological responses under projected global warming remain unknown. Heat stored in the water column in chemically stratified Antarctic lakes that have middepth temperature maxima can significantly influence the ice thickness trends via upward heat flux to the ice/water interface. We modeled the ice thickness of the west lobe of Lake Bonney,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
(116 reference statements)
2
26
1
Order By: Relevance
“…Ice has a low thermal conductivity, limits heat loss in the atmosphere and allows solar heating of the water column to temperatures well above those of the overlying air: Ward Hunt Lake had under-ice water temperatures up to 7°C, yet air temperatures averaged around 1.7°C in July (Bégin et al 2020). This greenhouse effect has been modelled in other ice-covered lakes of the Arctic (Vincent et al 2008) and Antarctica (Obryk et al 2019).…”
Section: Physicochemical Variablesmentioning
confidence: 99%
“…Ice has a low thermal conductivity, limits heat loss in the atmosphere and allows solar heating of the water column to temperatures well above those of the overlying air: Ward Hunt Lake had under-ice water temperatures up to 7°C, yet air temperatures averaged around 1.7°C in July (Bégin et al 2020). This greenhouse effect has been modelled in other ice-covered lakes of the Arctic (Vincent et al 2008) and Antarctica (Obryk et al 2019).…”
Section: Physicochemical Variablesmentioning
confidence: 99%
“…The north-south gradient is accompanied by reducing precipitation, resulting in an increasing dependence on melting of glacial ice to provide meltwater, and a declining temperature, which reduces duration of free-flowing water, from several months in the northern parts to only a few days per year at 80 • S. Increasing aridity at higher latitude also results in a high proportion of endorheic lakes and ponds, within which salinization becomes prevalent. Lakes ( Figure 1X) and ponds in the colder inland parts of the continent can be covered with many meters of perennial ice [446], while those at lower latitudes may receive sufficient summer heat to often become seasonally ice-free [447].…”
Section: Antarctic Freshwater Habitatsmentioning
confidence: 99%
“…Threats to the unique biodiversity of Antarctica come primarily through changing climate. Warming is anticipated to fundamentally change some freshwater systems, for example, through the loss of ice cover [446], or enhanced connectivity through increased water flow [460]. Evidence of warming is already found in the Antarctic Peninsula lakes [447], and in continental Antarctica, increased meltwater generation is resulting in dramatic rises in the levels of endorheic lakes with clear examples where unique microbial communities have been lost [461].…”
Section: Antarctic Freshwater Habitatsmentioning
confidence: 99%
“…Recently, Obryk and others (2019) studied the ice thickness evolution of WLB using climate scenarios based on historical extremes of locally observed solar radiation, surface air temperature, relative humidity and wind speed froma 16-year meteorological record (1996–2012). Whereas we relied on General Circulation Model (GCM) projections for our future climate scenarios, Obryk and others (2019) selected the years that exhibited the maximum and minimum values of each meteorological variable (based on the annual mean), and then built future scenarios with different combinations of those years. Obryk and others (2019) found that the ice cover of WLB vanished between ~2025 and ~2055 when scenarios with maximum values of solar radiation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas we relied on General Circulation Model (GCM) projections for our future climate scenarios, Obryk and others (2019) selected the years that exhibited the maximum and minimum values of each meteorological variable (based on the annual mean), and then built future scenarios with different combinations of those years. Obryk and others (2019) found that the ice cover of WLB vanished between ~2025 and ~2055 when scenarios with maximum values of solar radiation, i.e. those observed during the ‘flood year’, were simulated.…”
Section: Introductionmentioning
confidence: 99%